Determination of Three-Dimensional Corrective Force in Adolescent Idiopathic Scoliosis and Biomechanical Finite Element Analysis - Guan, Tianmin; Zhang, Yufang; Anwar, Adeel; Zhang, Yufen; Wang, Lina (Frontiers in Bioengineering and Biotechnology, 2020)
Aims In this study we have considered the three dimensional corrective forces for correction of scoliosis by using a patient specific finite element model. Materials and methods An objective function of corrective forces in three-dimensional space was defined. Computed tomography images were used to reconstruct three dimensional model of scoliotic trunk. Computer aided engineering software Abaqus was used to establish finite element model of deformed spine and its biomechanical characteristics were analyzed. By adjusting magnitude and position of corrective forces, objective function was minimized to achieve best orthopedic effect. The proposed corrective conditions were divided into three groups: 1. thoracic deformity; 2. lumbar deformity; 3. both thoracic and lumbar deformities were considered. Results In all three cases, the objective function was reduced by 58%, 52%, and 63%, respectively. The best correction forces point was located on convex side of maximum displacement of vertebral body. Conclusions Using minimum objective function method, spinal deformity in three-dimensional space can be sufficiently reduced. This study provides scientific basis for design of a new corrective brace for treatment of scoliosis.